2012
DOI: 10.1038/nature11055
|View full text |Cite
|
Sign up to set email alerts
|

An oxygen-regulated switch in the protein synthesis machinery

Abstract: SUMMARYProtein synthesis involves the translation of ribonucleic acid information into proteins, the building blocks of life. The initial step of protein synthesis consists of the eukaryotic translation initiation factor 4E (eIF4E) binding to the 7-methylguanosine (m7-GpppG) 5′cap of mRNAs1,2. Low oxygen tension (hypoxia) represses cap-mediated translation by sequestering eIF4E through mammalian target of rapamycin (mTOR)-dependent mechanisms3–6. While the internal ribosome entry site is an alternative transla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
391
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 286 publications
(410 citation statements)
references
References 31 publications
9
391
1
Order By: Relevance
“…The specificity of eIF4E and 4EHP for their mRNA targets and their affinities for the cap are influenced by binding partners (2,26,28). Thus, we used the BioID assay (29) to identify the eIF4E and 4EHP interacting proteins.…”
Section: Resultsmentioning
confidence: 99%
“…The specificity of eIF4E and 4EHP for their mRNA targets and their affinities for the cap are influenced by binding partners (2,26,28). Thus, we used the BioID assay (29) to identify the eIF4E and 4EHP interacting proteins.…”
Section: Resultsmentioning
confidence: 99%
“…Elegant studies by the Maxwell group (13) and others (14) revealed that HIF-2α mRNA is absent in human kidney tubule epithelia but present in dysplastic foci of the nephron. In these incipient renal tumor cells, HIF-2α may function as an oncoprotein (15), collaborating with, or activating, multiple growth-promoting pathways including cancer stewards c-myc (16), ras (17), and EGFR (18,19). Silencing of HIF-2α suppresses tumorigenesis of various genetically diverse cancers, further highlighting its central role in malignancy (16,17,20,21), although this depends on the experimental context (22).…”
mentioning
confidence: 99%
“…Testing interactions with components of this complex revealed that neither HIF-2α nor RBM4 interact with eIF4E or eIF4G, but they do interact with eIF4A and the eIF4E isoform 4E2, suggesting that the HIF-2α/RBM4 complex binds to an alternative capbinding assembly. eIF4E2, also known as 4E-homologous protein (4EHP) [6], does not interact with eIF4G and binds only weakly to 4EBP1, a factor that binds and inhibits eIF4E under hypoxia [2,[7][8][9]. The low affinity of eIF4E2 for 4EBP1 explains its resistance to inactivation in this metabolic condition.…”
mentioning
confidence: 99%
“…Cell function under hypoxia, however, is maintained by a significant degree of "residual" translation. In a recent article in Nature, Lee and colleagues show that the eIF4E homologue 4E2, in complex with the transcription factor HIF-2α and the RNA-binding protein RBM4, sustains cap-dependent translation during hypoxia [2]. Thus, by using a specialized isoform of eIF4E in complex with a hypoxia-induced RNP, the translational machinery preserves selective protein synthesis during stress ( Figure 1).…”
mentioning
confidence: 99%
See 1 more Smart Citation